A Handbook of Korean Zen Practice A Mirror on the Sŏn School of Buddhism (Sŏn’ga kwigam) - Hyu jeong 1520-1604; Jorgensen, John 1952- (Korean Classics Library: Philosophy and Religion, 2015)
Sŏn (Japanese Zen) has been the dominant form of Buddhism in Korea from medieval times to the present. A Handbook of Korean Zen Practice: A Mirror on the Sŏn School of Buddhism (Sŏn'ga kwigam) was the most popular guide for Sŏn practice and life ever published in Korea and helped restore Buddhism to popularity after its lowest point in Korean history. It was compiled before 1569 by Sŏsan Hyujŏng (1520–1604), later famed as the leader of a monk army that helped defend Korea against a massive Japanese invasion in 1592. In addition to succinct "ations from sutras, the text also contained "ations from selected Chinese and Korean works together with Hyujŏng's explanations. Because of its brevity and organization, the work proved popular and was reprinted many times in Korea and Japan before 1909.A Handbook of Korean Zen Practice commences with the ineffability of the enlightened state, and after a tour through doctrine and practice it returns to its starting point.